From Historic City to Heritage City. How to Construct Historical Continuity in the Buda Castle District. - Sonkoly, Gábor (Deutsches Institut für Urbanistik, 2021)
Der Autor modelliert in einer zeitgeschichtlichen, um 1900 beginnenden Analyse, wie sich das urbane Erbe (urban heritage) vom Schutz städtischer Monumente über die historische Rekonstruktion ganzer Stadtteile bis zur gegenwärtigen Perspektive auf historische Stadtlandschaften entwickelte und dazu je eigene Regime ausbildete. Besonders kritisch nimmt er in diesem Zusammenhang Stellung zur momentanen Praxis, Gebäude wie das Berliner Stadtschloss oder Teile des Budapester Schlossareals wiederherzustellen und damit eine neue (a)historische Interpretation zu forcieren. Sein Beitrag unterstreicht, wie diese Art der „heritagization“ oftmals im Widerspruch zur eigentlichen geschichtlichen Entwicklung der Städte steht und kritische Fragen zur historischen Kontinuität aufwirft.

In the last two decades, urban heritage has become omnipresent through the heritagization of thousands of cities and urban quarters all over the world and a complex (holistic) phenomenon encompassing all aspects of urban existence. Consequently, it has become a rival to urban history in terms of interpretation and experience of the urban past as well as a legitimate and spectacularly expanding research topic for urban history. This article examines the possible models of temporality integrated into the model of „regimes of urban heritage“ to render the evolution of urban heritage suitable for historical analysis. The current regime is characterized by an ahistorical ‘management of change’ approach. It regards historically layered cities as temporal and spatial continuums. One of the many consequences is the vast amount of urban (monument) reconstruction that was previously impossible to implement. In addition, significant changes have come to light in current historical interpretations and in the role of urban history in general. Hence, the continuous time of urban heritage and the deconstruction of the principle of authenticity proper are true challenges to historical time based on temporal ruptures and the critical urban history approach. These challenges will be explored by analyzing the example of the reconstruction of Buda Castle District.
Keywords: Historische Stadt; Historisches Gebäude; Rekonstruktion; Kulturerbe; Städtebaulicher Denkmalschutz; Denkmalpflege; Authentizität; Geschichtsverständnis; Planungskritik; Historische Rekonstruktion